2000
DOI: 10.2174/1389200003339171
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronosyltransferases

Abstract: Glucuronidation represents a major pathway which enhances the elimination of many lipophilic xenobiotics and endobiotics to more water-soluble compounds. The UDP-glucuronosyltransferase (UGT) family catalyzes the glucuronidation of the glycosyl group of a nucleotide sugar to an acceptor compound (aglycone) at a nucleophilic functional group of oxygen (eg, hydroxyl or carboxylic acid groups), nitrogen (eg, amines), sulfur (eg, thiols), and carbon, with the formation of a beta-D-glucuronide product. At this time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
369
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(379 citation statements)
references
References 0 publications
8
369
1
1
Order By: Relevance
“…It is reported that the amounts of UGT mRNA isoforms in liver of rats are variable [15], but the enzyme activity of UGTs is predominantly dependent on the expression of UGT1A1, 1A6 and 1A7 mRNAs [16]. In this study, the mRNA levels of UGT1A6 and 1A7 were significantly increased in the liver of rats with chronic hepatic failure, whereas that of UGT1A1 was significantly decreased (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…It is reported that the amounts of UGT mRNA isoforms in liver of rats are variable [15], but the enzyme activity of UGTs is predominantly dependent on the expression of UGT1A1, 1A6 and 1A7 mRNAs [16]. In this study, the mRNA levels of UGT1A6 and 1A7 were significantly increased in the liver of rats with chronic hepatic failure, whereas that of UGT1A1 was significantly decreased (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…K m values in this range are not unusual for xenobiotic aglycones (King et al, 2000), suggesting a low affinity of these substrates for glucuronidation, however these K m values are considerably higher than the 1 μM K m value for 3-hydroxy-benzo(a)pyrene found with channel catfish intestinal microsomes (James et al, 2001). Comparison of the V max values for OH-MXC and HPTE shows that V max is higher for OH-MXC, and suggests that OH-MXC will be more readily glucuronidated than HPTE in the catfish liver.…”
Section: Kinetics Of Glucuronidation Of Oh-mxc and Hptementioning
confidence: 85%
“…UGTs are also expressed in a wide variety of tissues, including brain, prostate, uterus, breast, placenta and kidney, to name only a few. 11,[76][77][78][79][80] The molecular genetics of human UGTs is now more clearly understood, with evidence for the existence of distinct subfamilies, which comprise more than 26 genes or cDNAs (Figure 2). Eighteen of them correspond to functional proteins and are encoded by two gene families, UGT1 and UGT2 that are, based on their sequence similarities, further divided into three subfamilies: UGT1A, UGT2A and UGT2B (for detailed information see Mackenzie et al 81 ).…”
Section: A Brief Overview Of the Glucuronidation Pathway And Human Ugtsmentioning
confidence: 99%
“…The UGT2B7 protein is also found in the brain, kidney, pancreas, mammary gland, lung and gastrointestinal tract, and several additional tissues. 80,134,138,[144][145][146] A cytosine to thymine polymorphism at base pair 802, leading to a histidine (H) 268 to tyrosine (Y) amino-acid substitution (UGT2B7*2), has been identified. 147,148 Data from large genotyping studies suggest that approximately one-third of the Caucasian population expresses the variant UGT2B7*2/*2 genotype (Table 5).…”
Section: Ugt2b7mentioning
confidence: 99%